Distributing the Benefits from the Commons: Square-Root Formula - Joaquim Silvestre (University of California, Department of Economics, 1995)
How should the benefits of the commons, say a publicly owned fishing resource, be distributed? A first possibility is equal division among the population. A second option is to distribute them among the people who actually exploit the resource in proportion to their activity level: this is the ""land to the tiller"" view. A third approach is the nusufruct"" view, by which a consumer of the fruits of the commons ends up contributing the average cost, whithout generating incomes for nonconsumers. The usufruct and ""land to the tiller"" views are polar opposites. One could consider intermediate positions where a fraction 0 of the benefits is distributed among consumers in proportion to their consumption, and the fraction 1-0 is distributed among fishers in proportion to their fishing effort. The paper singles out a particular value for 0 based on equalizing the ""rate of return,"" defined as follows. Consumers are the direct users of the fruits of the resource: they contribute numeraire (transferred to the fishers) and obtain fish in return. A fisher contributes time and obtains numeraire in return. It turns out that, if the ""return ratios"" are equalized across persons, fishers and consumers alike, then a particular value of 0 results, namely:
Keywords: 330